(Re)writing History in Byzantium A Critical Study of Collections of Historical Excerpts - Manafis, Panagiotis (Routledge Research in Byzantine Studies, 2020)
Scholars have recently begun to study collections of Byzantine historical excerpts as autonomous pieces of literature. This book focuses on a series of minor collections that have received little or no scholarly attention, including the Epitome of the Seventh Century, the Excerpta Anonymi (tenth century), the Excerpta Salmasiana (eighth to eleventh centuries), and the Excerpta Planudea (thirteenth century). Three aspects of these texts are analysed in detail: their method of redaction, their literary structure, and their cultural and political function. Combining codicological, literary, and political analyses, this study contributes to a better understanding of the intertwining of knowledge and power, and suggests that these collections of historical excerpts should be seen as a Byzantine way of rewriting history.